Kritik Sosial dalam Film Berjudul Wicked: Sebuah Pendekatan Analisis Semiotik - Gita Melinnia Sisiana; Febrian Febrian (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
The film "Wicked," adapted from the novel by Gregory Maguire, offered a new perspective on the character Elphaba, who was known as the wicked witch in the classic story "The Wizard of Oz." This research aimed to explore how Elphaba's character challenged the negative stereotypes associated with her and highlighted the importance of representing complex characters in media. This study was descriptive in nature, employing a semiotic approach to analyze the signs and meanings contained within Elphaba's character, as well as the social critique implications that arose. The findings indicated that Elphaba was not merely perceived as a symbol of evil but also served as a representation of empowerment for marginalized individuals, reflecting the complexities of identity and the struggle against social stigma. Elphaba's character illustrated a journey of transformation from ostracism to self-acceptance, inspiring audiences to understand and appreciate diversity and the challenges faced by those considered different. The film invited viewers to reflect on how societal judgments were often based on physical appearance and encouraged them to celebrate differences. The implications of this social critique were significant, as they could foster empathy and positive change within society, as well as raise awareness of the importance of embracing individual uniqueness.